Redbanded Thrips, Selenothrips rubrocinctus (Giard) (Insects: Thysanoptera: Thripidae) - Harold A. Denmark; D. O. Wolfenbarger (EDIS)
This document is EENY-099 (originally published as DPI Entomology Circular No. 108), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.